2008
DOI: 10.2346/1.2965831
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Pattern Optimization Based on Performance Prediction Tools

Abstract: Due to shorter development cycles and high cost pressure, the tread pattern development process is optimized by an analysis tool, which can predict the influence of the tread pattern on several tire properties. By using this tool conventional development cycles can be substituted by several virtual development cycles. The tool modules for the tire properties traction, handling, plysteer residual aligning torque (PRAT), groove wander, and noise are presented in this paper. The applicability of evolution strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…For extreme cases, a ratio of only 75% of longitudinal stiffness in relation to lateral stiffness can be assumed in the case of Scandinavian soft winter tires; see [3].…”
Section: Description Of Test Proceduresmentioning
confidence: 99%
“…For extreme cases, a ratio of only 75% of longitudinal stiffness in relation to lateral stiffness can be assumed in the case of Scandinavian soft winter tires; see [3].…”
Section: Description Of Test Proceduresmentioning
confidence: 99%
“…This has usually been calculated according to a predefined convergent objective function in previous research. [13][14][15][16][17][18] Therefore, the potential of the optimization algorithm can be limited because of its convergence characteristic as regards the predefined target. For example, even when the optimization algorithm has a sufficiently high potential to optimize the tyre pitch sequence, if the objective function has already achieved the predefined target, the optimization process must stop.…”
Section: Design Of a Divergent Objective Functionmentioning
confidence: 99%
“…The computational load is relatively low in this method and the effects of minor pitch elements on the tyre pitch length can be ignored owing to the limitations of the Fourier transform method; however, this is not true for the groove elements, which are one of the major pattern elements. An image-based analysis method 15 was introduced to predict the tyre air-pumping noise directly by modelling the air pumping in a pixel-based image format. This method makes it possible to consider the effects of the depth and the minor pitch elements in detail with a relatively small amount of computation.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the tread-block-structure form affected its grounding pressure and deformation characteristics, and reasonable control of the tread-block structure can effectively improve the tire grip-performance. Mundl et al [ 8 ] showed that the tread-pattern structure affects the tread stiffness of the tire, thus changing the tire’s grip performance. Therefore, the optimization of the tread-pattern structure can effectively improve the tire grip-performance.…”
Section: Introductionmentioning
confidence: 99%